Seeing Images, Reading Images: Circularity, Mirroring and the Artwork in Dario Argento’s Cinema - Giulio Luciano Giusti (Modern Languages Open)
Since Dario Argento’s directorial debut, The Bird with the Crystal Plumage, visual composition has played a key role in his work, as has the strict correlation between visual perception and image interpretation. Specifically, what emerges from Argento’s filmography since the early 1970s is the director’s ability to play with the ambivalence of pictorial images and techniques within a film in a specific duality that serves narrative purposes on the one hand, while challenging the self-enclosed mediality of classical cinematic narration on the other. In this regard, the diegetic art-historical repertoire, as well as the pictorial iconography and techniques displayed in Argento’s oeuvre, appear to transfer the dramatic tension from the narrative to the cinematic language, making the images the ultimate riddle to be solved. In a chosen corpus of the director’s work, it is evident that this ambivalence is already a prominent theme from the opening credit sequences. These sequences serve both a narrative and metanarrative function by foreshadowing the main themes of the films in question, and by serving as introductions to the aesthetic “textures” of the films through visual representation. The purpose of this article is to examine specific instances in Argento’s oeuvre, namely Four Flies on Grey Velvet, Deep Red, Trauma and, most notably, The Stendhal Syndrome, where the visual symbols and methods shown in the opening credit sequences serve the defined metanarrative objectives. Additionally, it aims to explore the extent to which this metanarrative function of artistic references extends beyond the opening credits in these films. The director’s cinema exhibits aesthetic and narrative circularity by repeatedly framing and reworking the same visual motifs developed in the opening credits in mirror-like sequences throughout key scenes. These motifs ultimately resurface in the epilogue, serving as a clear example of this circularity. This article demonstrates how these examples from Argento’s work exemplify the core of the director’s comprehensive production of a harmonious integration of narrative and visuals, which can effectively communicate a self-reflexive message about the essence of the shown images and their potential interpretation.